Connective negation and negative concord in Balto-Slavic - van der Auwera, Johan; Nomachi, Motoki; Krasnoukhova, Olga (Vilnius University Open Series, 2021)
With negative indefinite pronouns the Balto-Slavic languages all exhibit strict negative concord. In this study we investigate how negative concord functions in a context in which a connective negator (‘neither ... nor’) combines either phrases or clauses. We show that there are various types of non-concordant patterns.